Fairness and the optimal allocation of ownership rights - Ernst Fehr; Susanne Kremhelmer; Klaus M. Schmidt (Center for Economic Studies and ifo Institute (CESifo), 2005)
We report on several experiments on the optimal allocation of ownership rights. The experiments confirm the property rights approach by showing that the ownership structure affects relationship-specific investments and that subjects attain the most efficient ownership allocation despite starting from different initial conditions. However, in contrast to the property rights approach, the most efficient ownership structure is joint ownership. These results are neither consistent with the self-interest model nor with models that assume that all people behave fairly, but they can be explained by the theory of inequity aversion that focuses on the interaction between selfish and fair players.
Keywords: J3; C9; C7; 330; ownership rights; double moral hazard; fairness; reciprocity; incomplete contracts; Eigentumsrechtstheorie; Allokation; Joint Venture; Experiment; Moral Hazard; Gerechtigkeit; reciprocity